2008
DOI: 10.1002/jso.20967
|View full text |Cite
|
Sign up to set email alerts
|

Sequential treatment for recurrent localized prostate cancer

Abstract: To compare toxicity and efficacy of both salvage prostatectomy and salvage radiotherapy for prostate cancer a retrospective analysis was conducted. Thirty-two and 41 patients were treated with external beam radiotherapy or prostatectomy for cT1c-T2 prostate cancer later requiring salvage surgery or radiotherapy. Salvage surgery was performed when a local recurrence was biopsy confirmed and life-expectancy was more than 10 years. Salvage external beam radiotherapy was performed when PSA rose over 0.1 ng/ml in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
(34 reference statements)
0
16
0
4
Order By: Relevance
“…It was shown that 10‐year cancer control rates did not differ significantly between patients who underwent radiation therapy followed by salvage RP and those who underwent RP followed by salvage radiation therapy. However, urinary continence and erectile function were better preserved in patients undergoing salvage radiotherapy after surgery than in patients undergoing salvage prostatectomy after radiation [22]. This finding of a better quality of life for those patients treated with surgery followed by adjunctive radiotherapy could also have contributed to a higher acceptance of RP for treating high‐risk patients’ tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that 10‐year cancer control rates did not differ significantly between patients who underwent radiation therapy followed by salvage RP and those who underwent RP followed by salvage radiation therapy. However, urinary continence and erectile function were better preserved in patients undergoing salvage radiotherapy after surgery than in patients undergoing salvage prostatectomy after radiation [22]. This finding of a better quality of life for those patients treated with surgery followed by adjunctive radiotherapy could also have contributed to a higher acceptance of RP for treating high‐risk patients’ tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Van Der Poel et al . [22] recently reported the effectiveness and morbidity of sequential treatment of patients with recurrent localized PCa. It was shown that 10‐year cancer control rates did not differ significantly between patients who underwent radiation therapy followed by salvage RP and those who underwent RP followed by salvage radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, toxicity of salvage RT with total doses of about 70 Gy is low with less than 3% of late grade 3 proctitis or genitourinary side effects, respectively. [19, 27, 33, 38]. …”
Section: Resultsmentioning
confidence: 99%
“…Combined modality treatment utilizing surgery, radiation treatment and systemic therapy is the standard of care in other cancers, such as colon and breast. Furthermore, the safety of RP followed by RT rather than the other way around has been previously emphasized …”
Section: What Are the Pros And Cons Of Radical Prostatectomy In Men Wmentioning
confidence: 99%
“…72 Although the cancer outcomes are good after salvage surgery, it is still true that RT is better tolerated after RP than the other way around in men requiring additional treatment for their aggressive prostate cancer. [74][75][76] What are the pros and cons of radical prostatectomy in men with high-risk prostate cancer?…”
Section: Salvage Prostatectomy After Failure Of Other Primary Therapiesmentioning
confidence: 99%